SOCS Proteins as Regulators of Inflammatory Responses Induced by Bacterial Infections: A Review - Duncan, Skyla A.; Baganizi, Dieudonné R.; Sahu, Rajnish; Singh, Shree R.; Dennis, Vida A. (Frontiers in Microbiology, 2017)
Severe bacterial infections can lead to both acute and chronic inflammatory conditions. Innate immunity is the first defense mechanism employed against invading bacterial pathogens through the recognition of conserved molecular patterns on bacteria by pattern recognition receptors (PRRs), especially the toll-like receptors (TLRs). TLRs recognize distinct pathogen associated molecular patterns (PAMPs) and play a critical role in innate immune responses by expressing several inflammatory genes. Thus, activation of immune cells is regulated by cytokines that use the Janus kinase/signal transducers and activators of transcription (JAK/STAT) signaling pathway and microbial recognition by TLRs. This system is tightly controlled by various endogenous molecules to allow for an appropriately regulated and safe host immune response to infections. Suppressor of cytokine signaling (SOCS) family of proteins is one of the central regulators of microbial pathogen-induced signaling of cytokines, principally through the inhibition of the activation of JAK/STAT signaling cascades. This review provides recent knowledge regarding the role of SOCS proteins during bacterial infections, with an emphasis on the mechanisms involved in their regulation of antibacterial immune responses. Furthermore, the implication of SOCS proteins in diverse processes of bacteria to escape host defenses and in the outcome of bacterial infections are discussed, as well as the possibilities offered by these proteins for future targeted antimicrobial therapies.